Structure refinement, hydrogen-bond system and vibrational spectroscopy of hohmannite, Fe3+2 [O(SO4)2]·8H2O. (2nd January 2018) - Ventruti, G.; Della Ventura, G.; Orlando, R.; Scordari, F.
Abstract: The crystal structure of hohmannite, Fe 3+ 2 [O(SO4 )2 ]·8H2 O, was studied by means of single-crystal X-ray diffraction (XRD) and vibrational spectroscopy. The previous structural model was confirmed, though new diffraction data allowed the hydrogen-bond system to be described in greater and more accurate detail. Ab initio calculations were performed in order to determine accurate H positions and to support the experimental model obtained from XRD data. Infrared and Raman spectra are presented for the first time for this compound and comments are made on the basis of the crystal structure and the known literature for sulfate minerals.